Systems of State Support for School District Capital Expenditures. Issues Related to Capital Outlay and Debt Service. Report No. F76-8 - Augenblick, John.; Education Commission of the States, Denver, CO. Education Finance Center ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
Over the past five years, many states have modified their systems for providing aid to local school districts for current operating expenses, but few changes have taken place in states' support of local districts' capital outlay expenditures. However, the issues surrounding capital expenditures are somewhat different from those involved in current expenditures. The purpose of this booklet is to document both the similarities and differences. Section 1 outlines the magnitude of capital need. Section 2 describes current systems of state support for capital outlay and debt service. Section 3 discusses important problems in state support for capital outlay. Section 4 examines several states to ascertain the impact of different support systems on capital expenditures. Section 5 summarizes the booklet and examines further alternatives for state provision of educational facilities. (Author/JG)
Availability: Education Finance Center, Education Commission of the States, 1860 Lincoln Street, Denver, Colorado 80295.
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
Sponsoring Agency: Spencer Foundation, Chicago, IL.
Contract Number: 400-76-0039.
ERIC Note: Some ports may be marginally legible due to small type.
May also be available online. Address as at 14/8/18
Keywords: Capital Outlay (for Fixed Assets); Educational Finance; Elementary Secondary Education; Finance Reform; State Aid; State Legislation; State School District Relationship; Tables (Data); Reports, Research